2023
DOI: 10.1007/s00415-023-11797-w
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry in the follow-up of patients undergoing EVT - prediction of space-occupying hemispheric infarction

Clara-Sophie Kossel,
Franca Kobus,
Matthias C. Borutta
et al.

Abstract: Background Despite benefits of endovascular treatment (EVT) for large vessel occlusion (LVO) ischemic stroke, space-occupying brain edema (BE) represents a detrimental complication. In critical-care settings, CT-imaging is needed for monitoring these patients. Yet, bed-side techniques with the potential to predict whether patients develop BE or not would facilitate a time- and cost-efficient patient care. We assessed clinical significance of automated pupillometry in the follow-up of patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…To date, no studies have analyzed the ability of AP to discriminate AIS patients from HS. The limited evidence focusing on patients with AIS confirmed that AP can detect sudden clinical/radiological worsening early, suggestive of intracranial hypertension in such populations [ 17 , 18 , 32 , 33 ]. A reduction in mean overall CV, DV, and CH [ 17 ], or at least one NPi < 3 [ 32 ], predicted the development of radiological/clinical evidence of brain edema in patients who underwent mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, no studies have analyzed the ability of AP to discriminate AIS patients from HS. The limited evidence focusing on patients with AIS confirmed that AP can detect sudden clinical/radiological worsening early, suggestive of intracranial hypertension in such populations [ 17 , 18 , 32 , 33 ]. A reduction in mean overall CV, DV, and CH [ 17 ], or at least one NPi < 3 [ 32 ], predicted the development of radiological/clinical evidence of brain edema in patients who underwent mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The limited evidence focusing on patients with AIS confirmed that AP can detect sudden clinical/radiological worsening early, suggestive of intracranial hypertension in such populations [ 17 , 18 , 32 , 33 ]. A reduction in mean overall CV, DV, and CH [ 17 ], or at least one NPi < 3 [ 32 ], predicted the development of radiological/clinical evidence of brain edema in patients who underwent mechanical thrombectomy. Similarly, at least one NPi value < 2.8 was able to predict neurological worsening in patients with large hemispheric ischemic/hemorrhagic strokes of the anterior circulation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The constriction velocity (CV) in response to a standardized light stimulus represents a quantitative measure of pupillary reactivity as assessed in the classical neurological examination. CV has been shown to correlate with clinical outcome after cardiac arrest (18, 19) as well as with space-occupying edema, midline shift, and intracranial pressure after neurovascular and traumatic neurological injury (15, 20, 21). Both CV and inter-eye differences in NPi have been used to predict the occurrence of delirium in acute care units (22, 23).…”
mentioning
confidence: 99%